Progress for the poor - Kenworthy, Lane (New York, 2011)
"One of the principal goals of antipoverty efforts should be to improve the absolute living standards of the least well-off. Progress for the Poor aims to enhance our understanding of how to do that, drawing on the experiences of twenty affluent countries since the 1970s.